Analysis of Factors Affecting Minimum Salary of Workers in Indonesia Using Binary Logistic Regression - Hadi, Surjo; Renaldi, Sahat; Trimono, Trimono; Susrama Mas Diyasa , I Gede (Information Technology International Journal, 2024)
Salary is an important indicator used to measure the compensation and recognition individuals receive for their contributions to the workforce. Investigating the factors that influence salary levels is an intriguing research area. This study uses a logistic regression approach to analyze the relationship and influence of job field, job level, company location, and tenure on workers' salaries in Indonesia. The research findings reveal that the variables of job level and company location have a significant relationship with the minimum salary level received by workers. Based on the logistic regression modeling results, the variables that influence the minimum salary level are the company location (foreign) and average tenure